2020
DOI: 10.1016/j.jinf.2020.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic profile for the detection of anti-SARS-CoV-2 antibodies using four immunochromatographic assays

Abstract: In order to fight the SARS-CoV-2 pandemic infection, there is a growing need and demand for diagnostic tools that are complementary and different from the RT-PCR currently in use. Multiple serological tests are or will be very soon available but need to be evaluated and validated. We have thus tested 4 immunochromatographic tests for the detection of antibodies to SARS-CoV-2. In addition, we assessed the kinetics of antibody appearance using these assays in 22 patients after they were tested positive by RT-PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 6 publications
2
56
0
2
Order By: Relevance
“…However, due to RT-PCR infr astructure limitations and lack of supplies, which limit the number of people with access of a diagnostic tests, a rapid serologic assay was develop to expand laboratories testing capacity and reach all the population [10]. In this line, several rapid tests based on immunochromatographic method for SARS-CoV-2 IgM/IgG antibody have been developed [8,11]. Nevertheless, to achieve the goal of help in public health, this test needs to be a well-validated diagnostic tool that are sensitive, rapid and speci ic for the detection of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to RT-PCR infr astructure limitations and lack of supplies, which limit the number of people with access of a diagnostic tests, a rapid serologic assay was develop to expand laboratories testing capacity and reach all the population [10]. In this line, several rapid tests based on immunochromatographic method for SARS-CoV-2 IgM/IgG antibody have been developed [8,11]. Nevertheless, to achieve the goal of help in public health, this test needs to be a well-validated diagnostic tool that are sensitive, rapid and speci ic for the detection of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…Demey, et al [11] using 4 different immunochromatographic rapid tests describe that this kind of diagnostic tool have good performance for the detection of antibodies after SARS-CoV-2 infection. However, Vásárhelyi, et al [12] found low ef icacy in a rapid immunochromatographic tests detecting IgM and IgG antibodies against SARS-CoV-2 virus, suggesting that this test should not be used in the differential diagnosis of coronavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic accuracy studies and clinical performance specifications should be driven by the actual purpose of test use. Of note, clinical sensitivity determined in validation studies can be considerably lower than manufacturer's claim, although clinical specificity tend to be more consistent [21,[25][26][27][28][29][30][31]. Key components when selecting samples for evaluating clinical performance include: patient setting (e.g., inpatient vs. outpatient), severity of cases (e.g., asymptomatic, moderately symptomatic, and severe), and timing of assessment (e.g., 1-2 months or, 3+ months after exposure to the virus).…”
Section: Recommendation [B2]mentioning
confidence: 91%
“…One major concern regarding the implementation of serological testing into clinical practice is the potential for cross-reactivity, especially given that over 90% of adults are estimated to have antibodies against other commonly circulating coronaviruses [11]. Many manufacturers and most available literature report minimal assay crossreactivity, although some false positives against endemic coronaviruses and other species have been reported [21,[25][26][27][28][29][30][31].…”
Section: Recommendation [B2]mentioning
confidence: 99%
“…Detectable amounts of antibodies appear in the patient’s blood after a few days of the initial onset of symptoms. Although on average IgM appears in detectable quantity after about 5 days, based on variations reported, that can be as late at 11–12 days after infection onset [ 151 , 152 , 153 ]. Even in a 4–5-day window period, one can be asymptomatic but highly contagious and can infect other people in the close surroundings.…”
Section: Challenges and Pitfallsmentioning
confidence: 99%